Tufas calcárias de Felipe Guerra: caracterização e classificação - Barbosa, Vanusa Antonia Castelo (2013)
The work presented here represents a geological, speleological and paleoenvironmental study of calcareous tufa deposits that occur in the municipality of Felipe Guerra, State of Rio Grande do Norte. The tufas studied are the dissolution of carbonate rocks Jandaíra Formation products. By definition these deposits are characterized by the precipitation of calcium carbonate at temperatures close to ambient, and high porosity organic material in the composition. In the region it was observed that the tufa formations are deposited on the sandstones of Açu Formation and present considerable amount of fossil casts of gastropods and vegetables. The deposits obtained were described as being of three types: micritic, intraclastic and fitoclástico. The micrites correspond to recent deposits or training, and the rest are thought to be the oldest. In tufa longer located in urban areas there are three caves whose genesis is associated with the development of fractures affecting the Potiguar Basin in post-Campanian period. The geochemical data show that tufa are basically formed by calcium carbonate in the form of calcite crystals. Isotopic analyzes indicate different deposition environments: environments influence of continental origin of waters and environments influence of oceanic origin waters. Five samples were analyzed by radiocarbon (14 C), four of them revealing the ages of holocenic to pleistocene. Only one sample extrapolated the method of limit. The correlation between the isotopic data and radiogenic leads us to conclude that the formation of tufa is associated with periods of high rates of rainfall and that the caves have upper age 40,000 years.